Front Office Service Recovery Di Hotel Wyndham Palembang - Hariman, Hariman (Politeknik Pariwisata Medan, 2023)
One way to find out guests' needs and wants is by listening to complaints. Complaints are usually received by hotels when a service failure has occurred. These results show that service recovery is a complex process where everything must be taken into account in ensuring that guests are happy when they check out. In this study, the determination of informants was carried out using purposive sampling technique. Informants in the study were determined to be parties who were considered capable of providing the information needed, namely Front Office employees at Wyndham Opi Hotel, Palembang. The purpose of this research is to analyze optimal guest satisfaction is important in operations in the Front Office Department at Wyndham Opi Hotel, Palembang, if guests have complaints during their stay at Wyndham Opi Hotel must be given a solution to their discomfort. Keywords: Front Office, Service, Recovery